A Review of Indonesian Nationality Law - Zendy Wulan Ayu Widhi Prameswari; Erni Agustin; Stefania Arshanty Felicia (Journal of Southeast Asian Human Rights, 2023)
Stateless people are often denied access to the same rights and services as citizens. Furthermore, statelessness is often the result of discrimination against women, an issue that SDGs aim to address. This paper analyses how the Indonesian Nationality Law protects children at risk of statelessness. It also raises some legal challenges when applying the law with regards to the country's SDG achievements. Discussion of the nationality law in Indonesia is not new, but scrutinising it in connection to Indonesia's achievement of SDGs has yet to be carried out by other authors. This paper is legal research using statute and conceptual approaches. The study shows that by reforming its nationality law, the Indonesian Government has allowed women to confer their nationality on their children equally with men. However, some challenges related to the implementation of this new law and its regulations still have the potential to cause issues of discrimination and statelessness for Indonesian children, which relates strongly to the issues addressed by SDGs. Additionally, this paper will be useful for the development of constitutional law, especially human rights and nationality laws in Indonesia. Keywords: Children’s Rights, Indonesian Nationality Law, Non-discrimination Principle, SDGs, Statelessness